Is load application necessary when using computed tomography scans to diagnose syndesmotic injuries? A cadaver study. Issue 2 (February 2020) - Krähenbühl, Nicola; Bailey, Travis L.; Weinberg, Maxwell W.; Davidson, Nathan P.; Hintermann, Beat; Presson, Angela P.; Allen, Chelsea McCarty; Henninger, Heath B.; Saltzman, Charles L.; Barg, Alexej
Highlights: Load application does not improve the ability of most measurements to diagnose syndesmotic injuries. Discrete anterior inferior tibio-fibular ligament and deltoid ligament injuries cannot be distinguished. While more complete injuries can be identified, identification of incomplete lesions is limited. Inter- and intra-observer agreement of measurements is dependent on the experience of the observer. Abstract: Background: Injuries to the distal tibio-fibular ligaments are common. While pronounced injuries can be reliably diagnosed using conventional radiographs, assessment of subtle syndesmotic injuries is challenging. This cadaver study determines the impact of loading on the assessment of incomplete and more complete syndesmotic injuries when using weightbearing computed tomography (CT) scans. Methods: Fourteen paired male cadavers (tibial plateau to toe-tip) were included. A radiolucent frame held specimens in a plantigrade position while both non-weightbearing and weightbearing computed tomography (CT) scans were taken. The following conditions were tested: First, intact ankles (Native) were scanned. Second, one specimen from each pair underwent anterior inferior tibio-fibular ligament (AITFL) transection (Condition 1A), while the contralateral underwent deltoid transection (Condition 1B). Third, the remaining intact deltoid or AITFL was transected from each specimen (Condition 2). Finally, the distal tibiofibular interosseous membrane (IOM) was transected in all ankles (Condition 3). Eight different measurements were performed to assess the integrity of the distal tibio-fibular syndesmosis on axial CT scans. Results: Load application had no impact on most measurements. While incomplete syndesmotic injuries could not be identified, cadavers with more complete injuries differentiated from native ankles when assessed using axial CT images. No significant difference was evident between discrete AITFL or deltoid ligament transection. Conclusions: In a cadaver model, load application had no effect on the assessment of the distal tibio-fibular syndesmosis in incomplete and more complete syndesmotic injuries. Only more complete injuries of the distal tibio-fibular syndesmosis could be identified using axial CT images.